Synthesis of CoxMg1–xAl2O4 as cobalt blue ceramic pigments by Pechini process - Tuyền, Trần Ngọc; Hải, Hồ Văn Minh; Hoàng, Nguyễn Đức (Hue University Journal of Science: Natural Science, 2019)
In the present paper, the cobalt blue ceramic pigments with formula CoxMg1–xAl2O4 (x = 0,1÷0,9) with the spinel structure of MgAl2O4 were synthesized using the Pechini process. The resulting powders were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and CIE L*a*b* color measurement. The results show that the pigments calcinated at 1100 °C for 60 minutes provide a single phase of spinel with a high degree of crystallinity. The blue color intensity increases gradually with the amount of substituted Co2+ ions. The resulting pigments meet industrial requirements in terms of physicochemical characteristics.